Modifikasi Turn-Milling Dengan Motor Servo Sebagai Penggerak Rotary Tools - Pepi Setya Bakti; Yohanes Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Turn-milling is a machining method with a system of merging turning and milling operations, where work-pieces and cutting tool perform rotary motion synchronously to optimize the disposal process of chip materials. Development of turn-milling can be done on the lathe and milling conventional machining. The purpose of this study is to modify a conventional lathe with a stationary cutting tool and use a single cutting edge into a rotary tool using 4 (four) cutting sides (multy point cutting). In the manufacture and installation of rotary tool on conventional lathes, tools are made portable and can work on tangential, orthogonal and co-axial turn-milling systems. For the orthogonal and co-axial operating system of the turn-milling are divided into up and down operating systems. In this research the phenomenon of material disposal process of the work-piece surface was investigated. In the process of turn-milling test, the chip was removed automatically as the turn of the cutting edge of the endmill cutting tool. By using a servo motor as one of the rotating tools, it is expected that it will be able to perform the feed without any rotation of the force on the tools.Keywords : Conventional lathe, Rotary tool, Turn-milling.